Peningkatan Pelayanan Kesehatan Jiwa Masyarakat Melalui Pemberdayaan Petugas Kesehatan dalam Penerapan Terapi Aktifitas Kelompok - Susanti, Amelia; Diana Arianti; Welly (Universitas Alifah Padang, 2025)
Mental health problems cause personality changes and severe social maladjustment so that schizophrenia sufferers experience personal, social, spiritual and physical maladjustment. One effort to help social problems of schizophrenia sufferers is to increase the role of nurses in the community. Efforts made are included in the duties of nurses, including conducting group therapy, such as group activity therapy (TAK). The purpose of this community service activity is to increase the role of nurses to achieve optimal mental health services in the Kuranji Health Center work area. Community service activities include providing materials, demonstrations and roleplays of the application of Group Activity Therapy using video screenings and TAK observation sheets for nurses at the Kuranji Health Center. This activity involved 13 nurses who worked at the Kuranji Health Center from December 2024 to January 2025. The results of this community service activity showed that 90% of participants were able to understand the concept of Group Therapy and TAK, 87% of participants were able to understand the role of nurses in Group Therapy and TAK, and 89% of participants were willing to carry out group activity therapy in the Kuranji Health Center work area according to the work section. It is hoped that the results of this activity will be one of the relevant interventions in improving the level of community mental health and increasing the role of nurses in mental health services in the community.